2019
DOI: 10.15252/emmm.201910515
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TGF βR2‐mutant tumors exposes vulnerabilities to stromal TGF β blockade in pancreatic cancer

Abstract: TGFβ is important during pancreatic ductal adenocarcinoma (PDA) progression. Canonical TGFβ signaling suppresses epithelial pancreatic cancer cell proliferation; as a result, inhibiting TGFβ has not been successful in PDA. In contrast, we demonstrate that inhibition of stromal TGFβR2 reduces IL‐6 production from cancer‐associated fibroblasts, resulting in a reduction of STAT3 activation in tumor cells and reversion of the immunosuppressive landscape. Up to 7% of human PDA have tumor cell‐specific deficiency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Taken together, this extensive study from Huang et al illuminates key features of PDAC biology, challenges to treatment intervention, and the need for a more personalized approach. Over the course of PDAC development, a supportive niche is constructed composed of an extensive network of intercellular interactions with “normal” stromal and immune cells making up the TME.…”
Section: Graphical Depiction Of the Proposed Tgfβ‐il‐6 Paracrine Signmentioning
confidence: 92%
See 3 more Smart Citations
“…Taken together, this extensive study from Huang et al illuminates key features of PDAC biology, challenges to treatment intervention, and the need for a more personalized approach. Over the course of PDAC development, a supportive niche is constructed composed of an extensive network of intercellular interactions with “normal” stromal and immune cells making up the TME.…”
Section: Graphical Depiction Of the Proposed Tgfβ‐il‐6 Paracrine Signmentioning
confidence: 92%
“…The comparison of PDAC development to dysfunctional wound healing is especially striking given the key role of cytokine transforming growth factor beta (TGFβ) in both processes. In this issue of EMBO Molecular Medicine, Huang et al comprehensively and elegantly demonstrate a novel strategy by which TGFβ receptor 2 (TGFβR2) blockade in the stromal compartment can successfully treat PDAC tumors without intact TGFβ signaling. TGFβ effects are largely context dependent and have been shown to shape the phenotype of PDAC and its associated TME through a dual role (Massague, ; Ligorio et al , ).…”
Section: Graphical Depiction Of the Proposed Tgfβ‐il‐6 Paracrine Signmentioning
confidence: 99%
See 2 more Smart Citations
“…In an in vitro melanoma model, CAFs produced MMPs, which resulted in the abrogation (through protein cleavage) of the activity of two cell surface proteins, MICA-A and MICA-B (MHC Class-I polypeptide-related sequence A/B), which are inducers of NK activation [141]. Furthermore, Huang et al demonstrated that TGF-β-induced secretion of IL-6 from CAFs inhibited NK cell activity in in vitro and in vivo murine PDAC models [142]. CAFs may also directly suppress NK cytotoxicity, as demonstrated by their ability to reduce NK secretion of perforins and granzymes as shown in an in vitro colorectal cancer model [143].…”
Section: Suppression Of Natural Killer Cellsmentioning
confidence: 99%